Relationship of Province Government Equipment, with Regency/City Government Equipment in Improving the Achievement of Education Development Indicators in Banten Province - Syaukani, Ahmad; Effendi, Khasan; Ngadisah, Ngadisah; Teguh, Priyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study examines the reality of the relationship between Provincial Government Apparatus and Regency/City Government Apparatus in Improving the Achievement of Education Development Indicators in Banten Province. Indicators of education development reflect the quality of human resources which is positively and significantly correlated with the level of welfare, so that the better the level of quality of human capital, the better the level of welfare. By using a case study method that refers to the main case, namely the relationship between Provincial Government Apparatus and Regency / City Government Equipment after the implementation of the distribution of government affairs in the field of education. In this study, various categories were found that formed the initial proposition of the concept of findings that could be put forward: first, the relationship between Provincial Government Apparatus and Regency/City Government Apparatus in improving the achievement of education development indicators in Banten Province seen from the aspect of authority and institutional "limited" by laws and regulations. Invitation and static mindset of bureaucratic implementers in the education planning and budgeting process. In the institutional aspect, there is no structural device that has the authority to provide guidance and supervision of the education administration of the district/city government. Second, the relationship between Provincial Government Apparatus and Regency/City Government Apparatus in improving the achievement of education development indicators in Banten Province seen from the aspect of regional planning and finance is indirect but is represented by regional apparatus in charge of regional planning and finance. Third, the relationship between Provincial Government Apparatus and Regency/City Government Apparatus in improving the achievement of education development indicators in Banten Province seen from the aspect of informal guidance and supervision.